High-grade endometrial carcinoma limited to the endometrium or a polyp: is adjuvant treatment necessary?. Issue 10 (13th September 2021) - Dallaire Nantel, Leonie; Renaud, Marie-Claude; Gregoire, Jean; Sebastianelli, Alexandra; Plante, Marie
Abstract : Objective: High-grade endometrial carcinoma limited to the endometrium or a polyp is a rare clinical entity. Currently there is no consensus on standard treatment. Thus, the goal of this study was to evaluate the clinical outcomes of patients with type II endometrial carcinoma without myometrial infiltration or limited to a polyp. Methods: We retrospectively identified type II endometrial carcinoma (FIGO endometrioid grade 3, serous, clear cell, mixed and carcinosarcoma) with spread limited to the endometrium or a polyp from April 2013 to November 2017. Medical records were reviewed for the following information: age at diagnosis, patient characteristics, type of surgery, histology, stage according to FIGO 2009 classification, adjuvant treatments, and site of recurrence. Descriptive statistics and the Kaplan–Meier estimate were used for analysis. Results: A total of 25 patients with a type II stage IA adenocarcinoma were included. All were surgically staged with total hysterectomy, salpingo-oophorectomy, and lymph nodes assessment. The median age at diagnosis was 69 years. All patients had either disease limited to the endometrium (60%) or a polyp (40%). Only four patients had lymphovascular space invasion (16%). The median follow-up was 44 (range 2–67) months. Six patients (24%) received vault brachytherapy only and all others received no adjuvant treatment after surgery (n=19, 76%). Three patients (12%) experienced recurrences at 15, 21, and 55 months after surgery. Following systemic treatment all are alive and disease-free. The 3-year progression-free survival and overall survival were 91% and 100%, respectively. Conclusion: Expectant management with surveillance alone following surgery appears to be safe for patients with high-grade endometrial carcinoma limited to a polyp or the endometrium without myometrial invasion.